Flexible Integrated Electrical Cables Based on Biocomposites for Synchronous Energy Transmission and Storage. (23rd February 2016) - Wang, Hua; Li, Fengshi; Zhu, Bowen; Guo, Lin; Yang, Yun; Hao, Rui; Wang, Hong; Liu, Yaqing; Wang, Wei; Guo, Xintong; Chen, Xiaodong
Abstract : It becomes increasingly important to develop integrated systems with the aim of achieving maximum functionality for the state‐of‐the‐art electronic devices. Here, a flexible integrated electrical cable is reported by incorporating biomaterials based fiber supercapacitors into a resistor–capacitor circuit. In this unique integrated configuration, the fiber electrodes are alternately winded along the twisted electric wires, which worked not only as scaffolding to support and strengthen the slight electrodes but also as separators to spatially confine them to avoid short circuit. It exhibits excellent electrochemical performance comparable to conventional transition metal compounds based cells, and can especially realize sophisticated applications in synchronous energy transmission and storage, presenting a new member for the integrated energy storage system family. Abstract : A flexible integrated electrical cable is successfully fabricated by incorporating biomaterials‐based fiber supercapacitors into a resistor–capacitor circuit. It exhibits excellent electrochemical performance comparable to conventional transition metal compounds based cells, and can especially realize sophisticated applications in synchronous energy transmission and storage, presenting a new member for the integrated energy storage system family.